Low energy availability and relative energy deficiency in sport: a systematic review and meta-analysis - Gallant, T. L.; Ong, L. F.; Wong, L.; Sparks, M.; Wilson, E.; Puglisi, J. L.; Gerriets, V. A. (Sports Medicine, 2025)
Introduction: Low energy availability (LEA) occurs when energy expenditure from athletic training and bodily functions exceeds caloric intake. This imbalance results in declines in athletic performance and increases the risk of injury. Relative energy deficiency in sport (REDs) is a condition that occurs when the energy deficit is severe enough to cause alterations to metabolic rate, menstrual function, immune function, bone health, protein synthesis, and cardiovascular function. Many athletes, particularly those competing in endurance, aesthetic, or weight-class sports, are adversely impacted by this condition. Objectives: This study aims to determine the prevalence of LEA and REDs among athletes and present the first secondary analysis of the impacts of these phenomena on sports performance and risk of injury. Methods: This systematic review was registered on PROSPERO (CRD42023469253). Literature searches were performed following PRISMA guidelines using PubMed, Embase, and Cochrane online databases. Inclusion criteria were articles discussing the prevalence of LEA or REDs, the impact of LEA or REDs on athletic performance, or the impact of LEA or REDs EA on injury. Results: A total of 59 studies met the inclusion criteria for this meta-analysis, and 2737 of 6118 athletes (44.7%) in 46 different studies were determined to have LEA, including 44.2% of female athletes and 49.4% of male athletes. In addition, 460 of 730 athletes (63.0%) in eight different studies were determined to be at risk of REDs. Athletes with LEA were found to have decreased run performance, training response, endurance performance, coordination, concentration, judgment, explosive power, and agility relative to athletes with normal energy availability, as well as an increased likelihood of absence from training due to illness. Studies had mixed results as to whether LEA increased the risk of injury in general. However, most studies concluded that athletes with LEA have impaired bone health and a higher risk of bone stress injuries. Discussion: To our knowledge, this is the first systematic review analyzing the impacts of LEA and REDs on athletic performance and risk of injury. Due to the high estimated prevalence of LEA among athletes, coaches may want to consider employing surveys such as the low energy availability in females questionnaire (LEAF-Q) to identify athletes at risk for LEA, as early identification and correction of LEA can prevent the development of symptoms of REDs, reduce the risk of impaired bone health and bone stress injuries, and help athletes optimize the performance benefits from their training.